1994
DOI: 10.1084/jem.180.4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 receptor signaling in human monocytes and U937 cells involves the activation of a phosphatidylcholine-specific phospholipase C: a comparison with chemotactic peptide, FMLP, phospholipase D, and sphingomyelinase.

Abstract: Interleukin 4 (IL-4) diminishes cytokine activation of human macrophage. IL-4 binding to monocyte IL-4R is associated with protein kinase C (PKC) translocation to a nuclear fraction. The cleavage of diacyglycerol (DAG), an activator of PKC, from membrane phospholipids was investigated to define the proximal events of IL-4R signaling. IL-4 induced a statistically significant time-and dose-dependent generation of DAG. The IL-4-triggered production of DAG was not derived from phosphatidylinositol 4,5-bisphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
(118 reference statements)
2
8
2
Order By: Relevance
“…Therefore, these data strongly suggest that the activation of PC-PLC, but not other phospholipases, is involved in IL-4-induced STAT6 activation. Our data are also in agreement with previous studies showing the ability of IL-4 to induce PC-PLC, but not PI-PLC, PLD, or phospholipase A activation (29).…”
Section: Inhibition Of Stat6 Activation By Pc-plc Inhibitorssupporting
confidence: 83%
See 4 more Smart Citations
“…Therefore, these data strongly suggest that the activation of PC-PLC, but not other phospholipases, is involved in IL-4-induced STAT6 activation. Our data are also in agreement with previous studies showing the ability of IL-4 to induce PC-PLC, but not PI-PLC, PLD, or phospholipase A activation (29).…”
Section: Inhibition Of Stat6 Activation By Pc-plc Inhibitorssupporting
confidence: 83%
“…D609 is a xanthogenate compound that has been shown to inhibit a PC-PLC (28,35). IL-4 has been reported to promote the activation of a PC-PLC, although its role in IL-4 signaling has not been defined (29). Because the concentration of D609 required to inhibit STAT6 activation corresponded with those reported to block PC-PLC (28,35), our data suggested that PC-PLC is involved in the activation of STAT6 by IL-4.…”
Section: Inhibition Of Stat6 Activation By Pc-plc Inhibitorssupporting
confidence: 55%
See 3 more Smart Citations